Rectal cancer treatment in a teaching hospital. Issue 1 (2nd January 2017) - Verdin, Vanessa; Weerts, Joseph; Francart, David; Jehaes, Constant; Magis, David; Magotteaux, Paul; Mattart, Laurine; Monami, Benoit; Wahlen, Christian; Markiewicz, Serge
Abstract: Background: Rectal adenocarcinomas surgery morbidity and mortality might be impaired by neoadjuvant therapy. We performed this retropsective study to be compared with the PROCARE study running afterwards. Methods: We performed a retrospective study of 95 patients operated on for rectal adenocarcinoma in a single institution during the period of 2007–2009. We used logistic regression to estimate the relationship between possible predictive parameters of anastomotic leakage (AL). Results: The laparoscopic approach is favored in 63.1% of the cases with a conversion rate of 11.6%, mainly in man (6 out of 7). For low rectal cancer though, laparotomy was the first choice (92.3%). From a carcinological point of view, laparoscopy allowed a complete tumor resection according to the PME ( n  = 27) and TME ( n  = 26) standards. Multivariate analysis revealed that women, lower BMI, lower rectum tumor, laparoscopic surgery, neoadjuvant treatment and anal suture were associated with higher risk of AL. The mean hospital stay was 15.4 days (3–46 days) with an in-hospital mortality rate of 3.1%. Adjuvant chemotherapy was completed in 42.1% of the patients. Despite these treatments, we registered a recurrence rate of 26.6%. Of these, 72% were distally localized and 12% exclusively locally. Among the patients operated on by laparoscopy, there was one local recurrence and one local with distant metastases (3.7%). The one- and three-year survival rates were 91.5% and 80.4%, respectively. Conclusions: Our study showed a higher rate of AL than expected (18%). In our series recorded in PROCARE-Home, our leak rate has dropped to 10%. It may be indicating a positive effect of PROCARE.